An introduction to OTLA - Julie Gibbings-Garrett (Teaching in Lifelong Learning: A Journal to Inform and Improve Practice, 2018)
The Education & Training Foundation (ETF) is the government-backed, sector-owned national professional development body for the Further Education (FE) and training sector. Our role is to support the continuing transformation of our technical and vocational education system by ensuring the sector has world-class leaders, teachers, and trainers. It is the expectation that this leads to ever-improving learner outcomes, a more highly-skilled workforce for employers, and a stronger economy, country, and society. We do this by improving, driving, and championing the quality of leadership, teaching, and training.